2012
DOI: 10.3390/molecules17010598
|View full text |Cite
|
Sign up to set email alerts
|

Daphnoretin Induces Cell Cycle Arrest and Apoptosis in Human Osteosarcoma (HOS) Cells

Abstract: In this study antiproliferation, cell cycle arrest and apoptosis induced by daphnoretin in human osteosarcoma (HOS) cells were investigated. Antiproliferative activity was measured with the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay. The IC50 value of daphnoretin was 3.89 μM after 72 h treatment. Induction of apoptosis was evidenced by apoptotic body appearance and Annexin V-FITC/PI apoptosis detection kit. Flow cytometric analysis indicated daphnoretin arrested the cell cycle in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…Shan, Li, Li, & Zhang, 2015). Daphnoretin, a bicoumarin compound contained by S. chamaejasme L. (Peng et al, 2006), could induce apoptosis in HeLa cells in a mitochondria-mediated way , cause death of HOS cells by blocking cells successively in G2/M phases and activating the caspase-3 pathway (Gu & He, 2012), and so on (Jiang, Wu, Bai, Zhang, & He, 2014). Daphnoretin, a bicoumarin compound contained by S. chamaejasme L. (Peng et al, 2006), could induce apoptosis in HeLa cells in a mitochondria-mediated way , cause death of HOS cells by blocking cells successively in G2/M phases and activating the caspase-3 pathway (Gu & He, 2012), and so on (Jiang, Wu, Bai, Zhang, & He, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Shan, Li, Li, & Zhang, 2015). Daphnoretin, a bicoumarin compound contained by S. chamaejasme L. (Peng et al, 2006), could induce apoptosis in HeLa cells in a mitochondria-mediated way , cause death of HOS cells by blocking cells successively in G2/M phases and activating the caspase-3 pathway (Gu & He, 2012), and so on (Jiang, Wu, Bai, Zhang, & He, 2014). Daphnoretin, a bicoumarin compound contained by S. chamaejasme L. (Peng et al, 2006), could induce apoptosis in HeLa cells in a mitochondria-mediated way , cause death of HOS cells by blocking cells successively in G2/M phases and activating the caspase-3 pathway (Gu & He, 2012), and so on (Jiang, Wu, Bai, Zhang, & He, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Neochamaejasmin A arrests cell progression at the G1 phase and subsequent proliferation of human prostate cancer LNCaP cells (Liu et al, 2008). Daphnoretin, a bicoumarin compound contained by S. chamaejasme L. (Peng et al, 2006), could induce apoptosis in HeLa cells in a mitochondria-mediated way , cause death of HOS cells by blocking cells successively in G2/M phases and activating the caspase-3 pathway (Gu & He, 2012), and so on (Jiang, Wu, Bai, Zhang, & He, 2014). For S. chamaejasme L., it is an important scientific question to study the pharmacokinetics of the bioactive constituents after dosing to bridge the gap between the complex chemical composition of the herbal medicine and its medicinal effects.…”
Section: Introductionmentioning
confidence: 99%
“…This result is consistent with those expressed by Lee et al, where show that the expression of ALP in polymeric matrices of PCL with and without black phosphorus (BP, white phosphorus allotrope when treated at high pressures), does not have significant differences evaluated at days 1, 7, 14 and 21, and that the presence of BP slightly increases the ALP expression of MC3T3-E1 osteoblast cells 51 . In all coatings, it was possible to observe extended cell nuclei on the surface, without condensed and fragmented nuclei, which are typical morphological characteristics of an apoptotic cell [52][53][54] . This is related to the coatings that presented the lowest cell viability (PCL/CP/CNT 1.0 and 1.5 g/L), since as mentioned earlier, in this type of PCL coatings, cell viability decreases with increases in the CNT concentration.…”
Section: Discussionmentioning
confidence: 85%
“…Some of the 12-hydroxy-daphnane esters are known to activate protein kinase C (the tumour-promoting receptor site) [ 60 ] and are further claimed to possess anti-tumour activities in vivo against P-388 leukemia in mice [ 61 , 62 ]. Furthermore, the mechanism of antiproliferative activity of daphnoretin has been recently explored, showing that the compound causes death of human osteosarcoma (HOS) by blocking cells successively in G2/M phases and activating the caspase-3 pathway [ 63 ]. It has recently been shown that this compound displays antiviral activity [ 64 ], induces respiratory burst in rat neutrophils through protein kinase C activation [ 65 , 66 ] and is a well known antineoplastic agent (inhibits or prevents the proliferation of neoplasms) [ 67 ].…”
Section: Thymelaeaceae and Tribulaceaementioning
confidence: 99%